The integrative model of resiliency in higher education seekers in war conditions - V.V. Ogorenko; A.Ye. Nikolenko; T.Y. Shusterman; V.O. Kokashynskyi (Medičnì Perspektivi, 2023)
The article presents the results of the study of “The Integrative Model of Resiliency” in higher education seekers in war conditions. 174 higher education seekers were examined, among them: 144 students of the 4th-6th year of the medical faculty and the faculty of medicine and pharmacy of the Dnipro State Medical University, majoring in 222 “Medicine” (main group) and 30 students of the 4th-5th year of the Ukrainian State University of Science and Technology (comparison group). The aim of the study was to determine the modalities of resiliency in higher education seekers in the war condition. A psychodiagnostic method with the integrative model of resiliency “BASIC Ph” was used in the research. The distribution of modalities, their degree of expression (scoring), gender features of the distribution of modalities and their correlations were studied. In the vast majority of higher education seekers, one modality of resiliency dominated (94% in the main group, 100% in the comparison group), which was cognitive modality (64% in the main group, 67% in the comparison group) as the most mature, adaptive and constructive way of overcoming the crisis, especially during the war. In 6% of the investigated ones in the main group, the dominance of two modalities was found, among which the cognitive strategy was once again the leading one (89%). Some gender features of the use of stress coping strategies were revealed. Thus, a statistically significant difference was observed between the indicators of the modalities “Belief”, “Emotions” and “Social support” among males and females of the main group and “Emotions” and “Imagination” in the comparison group (p<0.05). Analyzing the gender characteristics of the correlations of resiliency modalities, a more multifaceted model was found in medical students of male gender. The obtained data contribute to a deeper understanding of own personal strengths and the involvement of less developed ones by higher education seekers, aimed at strengthening and enriching their resources to overcome resiliency of war crisis. Thus, the results of the study should be taken into account when developing psychoeducational and psychocorrective measures and conducting psychological support for of higher education seekers in the conditions of war and post-war time.